Investigating the effects of waste oil and styrene-butadiene rubber on restoring and improving the viscoelastic, compatibility, and aging properties of aged asphalt. (1st February 2021) - Ren, Shisong; Liu, Xueyan; Fan, Weiyu; Qian, Chengduo; Nan, Guozhi; Erkens, Sandra
Highlights: (1) Viscoelastic behaviors, compatibility and aging properties of waste oil/SBR rejuvenated asphalt are investigated. (2) Waste oil adversely affects the rutting resistance and anti-aging performance of aged asphalt. (3) SBR further enhances rutting, fatigue, cracking and aging resistance performance of waste oil rejuvenated asphalt. (4) SBR has a good compatibility with waste oil rejuvenated asphalt. Abstract: The objective of this study is to estimate the effects of using waste cooking oil (WCO), waste engine oil (WEO) as well as styrene butadiene rubber (SBR) on the performance restoration and improvement for aged asphalt. The rheological properties of aged and rejuvenated asphalts were assessed using rotational viscometer (RV), dynamic shear rheometer (DSR) and bending beam rheometer (BBR) methods. Moreover, compatibility, aging properties and rejuvenation mechanism of rejuvenated asphalts were also explored. The results revealed that WCO and WEO both strengthened the viscous properties, fatigue and cracking resistance, but adversely affects the temperature sensitivity, rutting resistance, elastic recovery, compatibility and aging properties of rejuvenated asphalt. Meanwhile, adding SBR further improved the temperature sensitivity, high and low temperature performance, compatibility as well as aging resistance of rejuvenated asphalt. Besides, WCO rejuvenated asphalt had some advantages in fatigue cracking resistance performance, while WEO rejuvenated asphalt possessed better rutting resistance, creep recovery and compatibility. Furthermore, Fourier transform infrared (FTIR) spectroscopy test showed that the physical blending mainly determined the rejuvenation mechanism when both waste oil and SBR was used in aged asphalt. Considering overall performance of rejuvenated asphalt, the optimum dosage of waste oil and SBR were recommended as 10 wt% and 3 wt%, respectively.